Sustained Activation of Interferon Regulatory Factor 3 during Infection by Paramyxoviruses Requires MDA5 - Grandvaux, Nathalie; Guan, Xiaochun; Yoboua, Fabrice; Zucchini, Nicolas; Fink, Karin; Doyon, Priscilla; Martin, Lydie; Servant, Marc J.; Chartier, Stéfany (Journal of innate immunity, 2014)
Retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA5) are the main cytosolic sensors of single-stranded RNA viruses, including paramyxoviruses, and are required to initiate a quick and robust innate antiviral response. Despite different ligand-binding properties, the consensus view is that RIG-I and MDA5 trigger common signal(s) to activate interferon regulatory factor 3 (IRF-3) and NF-κB, and downstream antiviral and proinflammatory cytokine expression. Here, we performed a thorough analysis of the temporal involvement of RIG-I and MDA5 in the regulation of IRF-3 during respiratory syncytial virus (RSV) infection. Based on specific RNA interference-mediated knockdown of RIG-I and MDA5 in A549 cells, we confirmed that RIG-I is critical for the initiation of IRF-3 phosphorylation, dimerization and downstream gene expression. On the other hand, our experiments yielded the first evidence that knockdown of MDA5 leads to early ubiquitination and proteasomal degradation of active IRF-3. Conversely, ectopic expression of MDA5 prolonged RIG-I-induced IRF-3 activation. Altogether, we provide novel mechanistic insight into the temporal involvement of RIG-I and MDA5 in the innate antiviral response. While RIG-I is essential for initial IRF-3 activation, engagement of induced MDA5 is essential to prevent early degradation of IRF-3, thereby sustaining IRF-3-dependent antiviral gene expression. MDA5 plays a similar role during Sendai virus infection suggesting that this model is not restricted to RSV amongst paramyxoviruses.